'I will never love anyone like that again': cognitive behavioural therapy and the pathologisation and medicalisation of ordinary experiences. Issue 2 (29th November 2021) - Ratnayake, Sahanika
Abstract : Psychiatry has a long history of being criticised for the pathologisation and medicalisation of ordinary experiences. One of the most prominent of these critiques is advanced by Allan Horwitz and Jerome Wakefield who argue that instances of ordinary sadness in response to events such as bereavement, heartbreak and misfortune, are being mistakenly diagnosed as depression due to an increasing lack of consideration for aetiology and contextual factors. Critiques concerning pathologisation and medicalisation have not been forthcoming for psychiatry's close cousin, psychotherapy. Using Cognitive Behavioural Therapy, one of the most prominent schools of contemporary psychotherapy as a case study, I demonstrate that psychotherapy also contributes to medicalising and pathologising bereavement, heartbreak and misfortune.